Letter from Campbell Morfit to James Curtis Booth, March 13, 1851 - Morfit, Campbell (1851)
Campbell Morfit (1820-1897), a distinguished chemist and co-editor with James Curtis Booth (1810-1888) of the Encyclopedia of Chemistry (1850), writes of an accidental inhalation of chemicals that almost proved fatal to him.
Keywords: Booth, James Curtis, 1810-1888; Morfit, Campbell, 1820-1897; Chemists